Case Report: Onset of Type 1 Diabetes Mellitus in a Patient With Ulcerative Colitis and Sjogren’s Syndrome Under Euthyroid Hashimoto’s Thyroiditis - Takahashi, Kaio; Anno, Takatoshi; Matsuda, Akio; Kimura, Yukiko; Kawasaki, Fumiko; Kaku, Kohei; Tomoda, Koichi; Kawamoto, Hirofumi; Kaneto, Hideaki (Frontiers in Endocrinology, 2022)
Type 1 diabetes mellitus (T1DM) is often complicated with some other autoimmune disorders, and the complication of various autoimmune disorders is known as autoimmune polyglandular syndrome (APS). Once autoimmune thyroid disease is developed, various autoimmune diseases can be also brought about. Such phenomena are classified as APS type 3A to type 3D. In this report, we show the onset of T1DM subject with ulcerative colitis and Sjogren's syndrome. Most important and interesting point in this case is if we did not check her thyroid-associated antibody, we could not have diagnosed her as APS. From results of this case’s data, we thought that he suffered from APS type 3A, 3B and 3D variant. This case pointed out very clearly the importance to measure thyroid-associated antibody under various autoimmune-disease conditions even if thyroid hormones levels are euthyroid. Moreover, based on a strong linkage between inflammatory bowel disease and T1DM and compatibility with both T1DM and APS type 3, we think it possible that Hashimoto's disease is present under complicated conditions together with ulcerative colitis and T1DM. It would be important to repeatedly check thyroid-associated antibody even in euthyroid subjects especially under various autoimmune-disease conditions.